A Proposal to integrate social housing in the free market - Emília Malcata Rebelo (2002)
In this paper it is supported that the social housing policies should be integrated with the free market performance, in such a way that overall city re-qualification may be enhanced, assuring the lower social classes access to welfare dwelling conditions. It is presented the case study of the Oporto city (Portugal), where the obsolete law of rents not only does not solve the poverty problems, but also immobilises the urban regeneration processes, and (through the displacement of the housing demand to the acquisition sector) artificially improves the dwellings price levels.A proposal is made in order to redistribute the State and Oporto Municipality budget so that the poorest families can freely choose their dwellings in the free market, which not only surmounts the social stigmas, but also stimulates new construction and recovery of old buildings, stressing high quality building levels, and promoting quality of life to all citizens.